2005
DOI: 10.1210/jc.2004-2238
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Recessive Mutation in Fibroblast Growth Factor-23 Causes Familial Tumoral Calcinosis

Abstract: Gain-of-function mutations in fibroblast growth factor-23 (FGF23) are responsible for autosomal dominant hypophosphatemic rickets, a disorder of isolated renal phosphate wasting. Patients with the disorder display hypophosphatemia with normocalcemia as well as inappropriately normal 1,25-dihydroxyvitamin D [1,25(OH)2D3] concentrations. Reciprocally tumoral calcinosis (TC) patients are often hyperphosphatemic with inappropriately normal or elevated serum 1,25(OH)2D3 levels and have ectopic and vascular calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
138
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(150 citation statements)
references
References 16 publications
10
138
2
Order By: Relevance
“…(11) Conversely, low levels of iFGF23 and elevated levels of cFGF23 are found in familial tumoral calcinosis (FTC) and hyperphosphatemic hyperostosis syndrome (HHS). (12) FTC and HHS can result from homozygous mutations in the O-linked glycosyl transferase N-acetylgalactosaminyltransferase 3 (ppGalNAcT3), a member of the galactosaminyl transferase family that is known to transfer N-acetylgalactomine residues to specific serine/threonine residues. (13) It has been shown that mutations in ppGalNAcT3 lead to a loss of FGF23 glycosylation and enhanced cleavage of FGF23, resulting in very low levels of iFGF23 and correspondingly high cFGF23 levels.…”
Section: Introductionmentioning
confidence: 99%
“…(11) Conversely, low levels of iFGF23 and elevated levels of cFGF23 are found in familial tumoral calcinosis (FTC) and hyperphosphatemic hyperostosis syndrome (HHS). (12) FTC and HHS can result from homozygous mutations in the O-linked glycosyl transferase N-acetylgalactosaminyltransferase 3 (ppGalNAcT3), a member of the galactosaminyl transferase family that is known to transfer N-acetylgalactomine residues to specific serine/threonine residues. (13) It has been shown that mutations in ppGalNAcT3 lead to a loss of FGF23 glycosylation and enhanced cleavage of FGF23, resulting in very low levels of iFGF23 and correspondingly high cFGF23 levels.…”
Section: Introductionmentioning
confidence: 99%
“…Its physiological importance is exemplified by numerous activating and inactivating mutations in the human FGF23 gene, causing two clinical disorders of disturbed Pi homeostasis: autosomal dominant hypophosphatemic rickets (ADHR, OMIM#193100; ADHR-Consortium 2000) and hyperphosphatemic familial tumoral calcinosis (HFTC, OMIM#211900; Benet-Pages et al 2005, Larsson et al 2005. Elevated FGF23 levels are also associated with several other disorders of hypophosphatemia or dysfunctional regulation of vitamin D, such as autosomal recessive hypophosphatemic rickets (ARHR; Feng et al 2006, Lorenz-Depiereux et al 2006, X-linked hypophosphatemic rickets (XLH; Liu et al 2003, Riminucci et al 2003, tumor-induced osteomalacia (TIO; Shimada et al 2001, White et al 2001b, fibrous dysplasia (FD; Riminucci et al 2003), and linear nevus sebaceous syndrome (LNSS; Hoffman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is often associated with hyperphosphatemia (Smack et al 1996), and is then termed hyperphosphatemic familial tumoral calcinosis (HFTC; MIM211900). HFTC has been shown to result from loss-of-function mutations in at least two genes: GAL-NT3 coding for UDP-N-acetyl-alpha-D-galactosamine: polypeptide n-acetylgalactosaminyltransferase 3 (ppGalNacT3) (Topaz et al 2004;Ichikawa et al 2005), a glycosyltransferase, which initiates O-glycosylation (Ten Hagen et al 2003);and FGF23 (Benet-Page`s et al 2005;Larsson et al 2005;Araya et al 2005;Chefetz et al 2005) coding for fibroblast growth factor 23 (FGF23), a potent phosphaturic protein (Berndt et al 2005).…”
Section: Introductionmentioning
confidence: 99%